(untitled) (International Journal of Nursing Education, 2024)
Introduction: The quality of life of stroke survivors is a major concern for healthcare providers due to the physical, psychological, and social issues caused by stroke. This study aims to identify the quality of life of post-stroke patients undergoing outpatient treatment at the neurology clinic of the General Hospital of South Aceh Regency, Indonesia. Methods: This research uses a cross-sectional study design with a sample of 120 respondents. All post-stroke patients undergoing treatment at the clinic were included in the study. Data were collected through face-to-face interviews at the specialized stroke clinic from January to March 2024. The research instrument used was the Indonesian version of the Stroke-Specific Quality of Life (SS-QoL) questionnaire, which has been validated. The reliability test of the SS-QoL resulted in a Cronbach’s Alpha value of 0.920. Data analysis was conducted using a descriptive approach, including frequency distribution, percentage, standard deviation, and SS-QoL scale score distribution. Results: The study found that the majority of stroke patients’ quality of life was in the good category, amounting to 77.5%. The quality of life domain indicated that personality was the worst dimension (mean=3.13, SD=0.762), while family role, social role, mood, and energy were the best domains (mean=4.13, SD=0.766). Conclusion: The quality of life of stroke patients undergoing outpatient treatment at the Neurology Clinic of South Aceh General Hospital is predominantly in the good category. Interventions focusing on personality aspects need to be enhanced to further improve patients’ quality of life.